O real empírico e fílmico segundo Pasolini e Manoel de Oliveira - De Andrade, Ana Carolina Negrão Berlini [UNESP] (My University, 2014)
This work intends to do a short comparison between the film-makers Pier Paolo Pasolini and Manoel de Oliveira aesthetic ideas keeping the analysis of the relations held by both with the real empirical and filmic as the main focus. These aesthetic ideas were taken from texts written by the artists themselves and from interviews that were given in a time of their lives where the artistic ripeness had reached its roof which possibilities a kind of overview.
The real empirical and filmic according to Pasolini and Manoel de Oliveira
Keywords: Cinema; Manoel de Oliveira; Pier Paolo Pasolini